Coupled carbonation-rust formation-damage modeling and simulation of steel corrosion in 3D mesoscale reinforced concrete. (August 2015) - Nguyen, T.T.H.; Bary, B.; de Larrard, T.
Abstract: This paper presents a modeling strategy to simulate the corrosion of steel reinforcement in atmospheric environment due to carbonation of concrete. Its principal objectives are to analyze the effects of the progressive formation of corrosion products at the steel/concrete interface on concrete cover cracking. The approach is based on modeling studies carried out independently on carbonation, corrosion and creep. These models are coupled and integrated into a numerical 3D simulation procedure for investigating the behavior of concrete mesostructures. A viscodamage model is used to reproduce both creep and damage behaviors of mortar, and the approach is applied to the simulation of a 3D reinforced concrete mesostructure including explicitly the coarse aggregates. The numerical results highlight the influence of aggregates and the effects of creep on crack initiation and propagation.